Corpus-assisted discourse analysis of gendered lexical choice in Israel-Palestine conflict narratives - Suhandoko, Suhandoko; Nobair, Ach.; Sultansyah, M. Naufal; Al Aziz, Muhammad Farid; Dhiaulhaq, Naufal Wigi (Humanus, 2025)
Social media play a crucial role in shaping public discourse. Studies have been conducted to examine the language of digital spaces, however data-driven analyses of how gender construct the conflict narrative are surprisingly scarce. This study aimed to explore how gendered lexical differences in Twitter/X construct the narratives of the Israel-Palestine conflict. Employing a corpus-assisted discourse analysis, the study examines 2,105 tweets posted between 7 to 13 October 2023, a critical period when the conflict escalated. After pre-processing stage, we performed sentiment analysis using RapidMiner software to divide the corpora into four subsets: pro-Israel male and female sub-corpus and pro-Palestine male and female sub-corpus. After that, we performed keyword analysis using AntConc software to generate the word list. By extracting the twenty most frequent words along with the concordance lists, we abductively clustered the words to reveal the user’s thematic narrative. The findings reveal that male user mainly frame the conflicts around security, historical legitimacy, and territorial rights. On the contrary, female users are more likely construct their narrative on humanitarian issues. This suggests that culturally gendered norms play significant role in shaping the digital discourse, with male-driven narratives reinforcing securitization and female-driven narratives amplifying humanitarian consequences of the conflict.